Efeitos de demanda e de oferta na estrutura de capital de companhias abertas no Brasil - Campos, Anderson Luis Saber (2007)
From the theory on structure of capital and the application of structural equations a model was considered to evaluate the indebtedness of the public companies in Brazil. The effect of direct and indirect costs of bankruptcy, tax benefits, agency costs of free cash flow and the agency costs of borrowing. Computed the results, which was opted to analyzing an alternative model that indicates the relevance of the capital demand and offers effects in the level of companies indebtedness. One met evidences on the relevance of direct and indirect costs of bankruptcy and agency costs of borrowing in the determination of the capital structure in analyzed companies.